On the Scenes in the Sixth Tier of Vasil’evskie Gates - Bulkin, Valentin A. (Actual Problems of Theory and History of Art, 2015)
This article discusses the bas-relief scenes in the sixth tier of Vasil’evskie Gates of St. Sophia Cathedral in Novgorod, erected under the order of the Archbishop, Vasilii Kalika. It was in accordance with Vasilii’s direction that these four scenes from the Old Testament and Apocrypha (“Rejoicing of King David”, “Spiritual Scales of the Last Judgement”, “David and Goliath” and “Centaur Carries King Solomon in his Hands”) were placed into the circle of scenes from the Gospels. In particular, the scene of “Rejoicing of King David”, depicting the transfer of the Ark of the Covenant to the City of David by the King accompanied by his people, had a special meaning for the Archbishop of Novgorod. Vasilii must have seen parallels between his own life’s path of a commoner rising up to the position of a cathedral warden, and that of King David, a shepherd who became a king. Several other scenes from the sixth register may also be related to certain pivotal episodes of Archbishop Vasilii’s life. In addition, the author proposes that the construction of both Vasil’evskie Gates and the Church of the Entry of Our Lord into Jerusalem (1336–1337) were integral parts of a unified project conceived by the archbishop after his pilgrimage to Jerusalem and could also be linked to his theologically substantiated rethinking of the layout of the northern area of Detinets, including Archbishop’s Court and St. Sophia Cathedral.